2014
DOI: 10.3109/10826084.2014.913632
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acculturation on Substance Use Behaviors among Latina Sexual Minority Women: The Mediating Role of Discrimination

Abstract: Increased acculturation leads to substance use and this relationship is partially mediated by discrimination (Sobel test = 2.10; p < .05). CONCLUSIONS/IMPORTANCE: Implications of these findings and directions for future research are discussed. Funding was provided by several women's and public health organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Two studies focusing on discrimination had mixed findings. In a community-based sample of Latina SMW, Matthews and colleagues [78] found that more than 70% had ever used marijuana, 19% were heavy drinkers, 36% were current smokers, and more than 30% had ever used cocaine, crack, crystal meth, or heroin. Acculturation and discrimination (based on race/ethnicity, sexual identity, gender, or gender identity) were each independently and significantly associated with substance use; the association between acculturation and substance use was partially mediated by discrimination.…”
Section: Racial/ethnic Differences In Aod Usementioning
confidence: 99%
“…Two studies focusing on discrimination had mixed findings. In a community-based sample of Latina SMW, Matthews and colleagues [78] found that more than 70% had ever used marijuana, 19% were heavy drinkers, 36% were current smokers, and more than 30% had ever used cocaine, crack, crystal meth, or heroin. Acculturation and discrimination (based on race/ethnicity, sexual identity, gender, or gender identity) were each independently and significantly associated with substance use; the association between acculturation and substance use was partially mediated by discrimination.…”
Section: Racial/ethnic Differences In Aod Usementioning
confidence: 99%
“…Distal and proximal social stressors may include institutional discrimination, community prejudice, interpersonal violence, internalized stigma, and anticipation of maltreatment (Meyer, 2003, 2013) and are associated with increased hazardous and disordered alcohol use (e.g., Matthews et al, 2014; McCabe, Bostwick, Hughes, West, & Boyd, 2010; McLaughlin, Hatzenbuehler, & Keyes, 2010). Most U.S. states do not protect sexual minorities from workplace discrimination or hate crimes and sexual minorities living in in these states are more than twice as likely to have an alcohol use disorder (Hatzenbuehler et al, 2009).…”
mentioning
confidence: 99%
“…The depression, anxiety, and stress she was experiencing was a result of being a lesbian. The stress that Alejandra exhibited is experienced among many sexual minorities and has been well documented in the literature (Matthews et al, 2014;Meyer & Frost, 2013).…”
Section: Support Systemsmentioning
confidence: 91%